Determination of Islamic Leadership: Amanah, Fatonah, Tabligh, Siddiq - Taufik, Taufik (Green Publisher, 2023)
Termination of Islamic leadership:: Amanah, Fatonah, Tabligh, Siddiq are scientific literature review articles. Objective Writing this article to establish the influence hypothesis or the role between variables that will be used in further research, within the scope of Human Resource Management and Leadership. Article Writing Method is method library research, sourced from online media such as Google Scholar, Mendeley and media online other academics. Analysis qualitative descriptive. results of this article are: 1) Amanah has an effect on Islamic Leadership; 2) Fathanah influences Islamic leadership; 3) Tabligh influences Islamic leadership; 4) Siddiq influences Islamic leadership.